Assessment of Study Habit Skills and Peergroup Influence on Pupils Academic Performance in Mathematics in Lagos Division Nigeria - Omoshalewa Lasbat Badamas; Balagun Abdulrasaq Olatunji; Elizabeth O. Uyanne (Universitas Ahmad Dahlan, 2022)
Background: Technology is the mainstay of any societal development and Mathematics is seen as a tool for the community to achieve it. However, pupils’ performance in Mathematics have not been encouraging and this has been the concern of education stakeholders in the community. Contribution: This study therefore assessed the study habit and peer group influence on pupils’ performance in mathematics. Method: The sample comprised 450 basic-six pupils. Questionnaire and test were used to gather data. Research questions were answered using mean while research hypotheses were tested using PPMC. Results: Finding revealed that there was no significant relationship between study habit skills and pupils’ performance in Mathematics and there was significant relationship between peer group influence and pupils’ academic performance in Mathematics. Conclusion: It was recommended that schools should organize programmes for pupils to develop good study habit and to wary of the friends to be kept